Um relato de experiência: as leis municipais de inclusão aplicadas ao cotidiano de um centro municipal de ensino da cidade de Manaus - Ribeiro, Letícia de Carvalho (Brasil, 2025)
This study's central objective is to analyze how the inclusion of children on the autistic spectrum in early childhood education is promoted through specialized educational care, as well as to encourage dialogue and reflections through the report of experiences lived in the supervised internship in early childhood education, in the course full degree in Pedagogy, subsidized by the Federal University of Amazonas. The methodological procedures used will be descriptive research and field research, which were developed through reading scientific articles by authors who discuss the topic, analysis of municipal laws and data collected through research institutions, in addition to observation at the school of internship. The purpose of the research result is to direct the essential processes for inclusive special education that works effectively.